2021
DOI: 10.1080/13102818.2021.1941252
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of Cellulose-like synthase D gene family in Dendrobium catenatum

Abstract: Dendrobium catenatum, which grows on the semi humid rocks in the mountains, has been at the top of the 'Nine Immortals of China' since ancient times. It is a kind of yin tonic medicine and its main active component is polysaccharide. Cellulose synthase-like D(CslD) genes were predicted to catalyse the biosynthesis of 1,4-β-d-glycan backbone of hemicelluloses, which plays fundamental roles in plant development. To investigate the role of CslD in the development of D. catenatum, eight CslD genes (DcCslD1,2a,2b,3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…In Arabidopsis , the overexpression of CesA6 - like genes has been suggested to influence both cell expansion and division [ 22 ]. Furthermore, it has been reported that several cellulose synthase-like ( Csl ) genes promote cell division and affect cell cycle, including CslD5 during Arabidopsis stomatal lineage development [ 66 ] and in meristems [ 67 ], CslD1 in maize [ 68 ], CslDs ( CslD1 , CslD2a , CslD2b , CslD3a , CslD5 ) in Dendrobium catenatum [ 69 ], and CslD4 in rice [ 70 ]. The increase of all parameters related to the dimension of F 3 1 stem, leaves, and roots is in line with the above-mentioned results, suggesting that both cell division and cell expansion are increased in the F 3 1 line.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , the overexpression of CesA6 - like genes has been suggested to influence both cell expansion and division [ 22 ]. Furthermore, it has been reported that several cellulose synthase-like ( Csl ) genes promote cell division and affect cell cycle, including CslD5 during Arabidopsis stomatal lineage development [ 66 ] and in meristems [ 67 ], CslD1 in maize [ 68 ], CslDs ( CslD1 , CslD2a , CslD2b , CslD3a , CslD5 ) in Dendrobium catenatum [ 69 ], and CslD4 in rice [ 70 ]. The increase of all parameters related to the dimension of F 3 1 stem, leaves, and roots is in line with the above-mentioned results, suggesting that both cell division and cell expansion are increased in the F 3 1 line.…”
Section: Discussionmentioning
confidence: 99%
“…It is conserved in all terrestrial plants and is involved in various aspects of the plant life cycle, including polysaccharide synthesis ( Zhang et al, 2016 ; Yu et al, 2018 ; Zhan, 2019 ), responses to environmental stimuli ( Song et al, 2019 ), cell expansion and division ( Yang et al, 2016 ; Peng et al, 2019 ), as well as plant development ( Bernal et al, 2008 ; Luan et al, 2011 ; Yoo et al, 2012 ). Studies have shown that DcCslDs are differentially expressed in roots, stems, and leaves of D. catenatum using qRT-PCR ( Xi et al, 2021 ). The drought-resistant recovery treatment was closely related to the expression level of DcCslD5 , and low-temperature stress significantly affected the expression levels of DcCslD1, DcCslD2a, DcCslD2b, DcCslD3a , and DcCslD5 ( Xi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DcCslDs are differentially expressed in roots, stems, and leaves of D. catenatum using qRT-PCR ( Xi et al, 2021 ). The drought-resistant recovery treatment was closely related to the expression level of DcCslD5 , and low-temperature stress significantly affected the expression levels of DcCslD1, DcCslD2a, DcCslD2b, DcCslD3a , and DcCslD5 ( Xi et al, 2021 ). In our study, the CslD gene mainly expanded in epiphytic and partly in terrestrial orchids, but not in saprophytic orchids, which indicated that expansion of the CslD gene, which mainly synthesizes polysaccharides, might have promoted the adaptation of epiphytic orchids to extreme environments under positive selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations